Pengembangan Inovasi Desain Tenun Sebagai Produk Ekonomi Kreatif Melalui Pemasaran Digital Facebook di Desa Laranwutun - Arnold Moruk Pawarrangan; Urbanus Ola Hurek; Meylisa Yuliastuti Sahan (Lembaga Pengembangan Kinerja Dosen, 2026)
This MBKM program aims to develop innovative woven textile designs in Laranwutun Village, Ile Ape District, Lembata Regency, as an effort to enhance the economic value of local products through the utilization of digital marketing based on Facebook. Laranwutun Village possesses significant potential in traditional ikat weaving; however, artisans still face challenges in design development and rely on conventional marketing practices. The program was implemented over a two-month period involving MBKM students, local weavers, and MSME actors. The implementation methods included mentoring in creating innovative textile designs by combining traditional motifs with modern color trends, product photography training, and training on the use of Facebook for promotion and sales. The results indicate an improvement in artisans’ ability to create new designs, enhanced product visual quality, and expanded digital marketing reach. Following the training, five artisans actively utilized Facebook as a promotional medium and successfully received orders from outside the region.Overall, this MBKM activity contributes to strengthening the creative economy based on local culture and enhancing the independence of woven-textile entrepreneurs in Laranwutun Village through accessible and sustainable digital technology utilization.